Rozwój kompetencji 4K jako narzędzie adaptacji społecznej – metodyka pracy nauczycieli wychowania przedszkolnego i edukacji wczesnoszkolnej - Filipiak-Adamus, Katarzyna (Pedagogika Społeczna Nova, 2025)
The main aim of the article is to indicate a methodological solution in the work of preschool and early school teachers, that will serve the purpose of shaping the competences of the future, necessary for effective adaptation to the constantly changing reality. The foundation for the proper development and functioning of an individual who faces constant social changes is the need to modify one’s own set of competences – because the routine ones may turn out to be insufficient. In the light of such assumption, the 4K concept, authored by Jérémy Lamri, can be considered crucial. By enumerating the most important competencies of the future – creativity, communication, critical thinking and cooperation– Lamri argues that these are cognitive skills that facilitate one’s adaptation to new situations. Therefore, a necessary task for the years to come will be to thoroughly reconsider the ways of teaching and learning. One of the groups that bears this responsibility are teachers. In this article, I would like to pay special attention to the teaching methodology, which, due to its specificity, may contribute to the development and consolidation of 4K competences among students.